Diagonal compression testing of masonry under fatigue loading and high static loads - Karanikoloudis, Georgios (2023)
Underground railway operations pose a significant impact on overlying, highly sensitive historic masonry structures. Here, the process of structural assessment involves fatigue actions, through induced ground-borne vibrations, from operating underground railways. Considering long-term exposure periods, fatigue can introduce local cracking and losses, which endanger the integrity of both structural and non-structural elements. The lack of experimental fatigue data on tensile actions in masonry and the apparent computational restraints from constitutive cementitious material models that do not account for damage due to repeated loading, increase the complexity of structural assessment, under combined fatigue actions and other hazards. The current paper aims at providing new experimental data on fatigue in historic brick and lime mortar masonry wallets, replicating realistic combinations of static and fatigue loading under diagonal compression. Material deterioration and stiffness degradation are monitored throughout the process. Hence, under moderate amplitudes of fatigue loading and high static loads, cracking occurred, at a relatively low number of cycles, demonstrating the need for more strict vibration thresholds to ensure the integrity of historic masonry buildings.